Social Outcome and Quality of Life after Epilepsy Surgery in Hippocampal Sclerosis - Towachiraporn, Peerasin; Bunyaratavej, Krishnapundha; Limotai, Chusak (Thai Journal of Neurological Surgery, 2025)
Background: Quality of life is worse in patients with epilepsy as compared to that of general population. Although seizure freedom is the ultimate treatment goal in epilepsy surgery, patient’s expectations and improvement in quality of life may also include other social aspects such as education, employment, income, driving and social relationships. Objective: To investigated social outcomes, quality of life, social factors influencing quality of life, presurgical patient’s expectation and patient’s satisfaction after temporal lobe epilepsy (TLE) surgery. Methods: Seventy-three patients with medically refractory hippocampal sclerosis (HS) who underwent epilepsy surgery between January 2014 and December 2019 at King Chulalongkorn Memorial Hospital (KCMH) were evaluated. The socioeconomic data was collected from the subjects and their caregivers by a questionnaire–interview. All patients had completed at least 2-year postoperative follow-up. Results: There were 27 males (37%) and 46 females (63%) with mean age of 35.82 ± 10.14 years at the time of surgery. Seventy-one (97%) patients underwent standard anterior temporal lobectomy. Sixty-six (90.41%) patients reported excellent seizure outcome (ILAE Class I). For social outcome, there were significant changes in driving status (45.21 vs 60.27%, p = 0.008) but there was no significant change in other aspects (education, employment, income, marital status) after surgery. All patients reported excellent postoperative quality of life. The factors which were associated with better quality of life following surgery were employment (p = 0.036) and ability to drive (p = 0.006). Sixty-four (88%) patients cited seizure control as their main expectation. Sixty-seven (91.78%) patients were satisfied with surgery and would suggest other patients to pursue similar surgical treatment. Conclusions: Surgery for medically refractory temporal lobe epilepsy improves social outcomes in driving aspect. Gaining employment and ability to drive after surgery are important factors influencing better quality of life. Vocational and driving rehabilitation program should be included in comprehensive epilepsy treatment program in order to enhance postoperative quality of life in TLE patients.